Penerapan Informasi Akuntansi dan Tingkat Penerimaan Dana Zakat Pada Badan Amil Zakat Nasional Medan - Yasmi Fazrah; Yenni Samri Juliati Nasution; Arnida Wahyuni Lubis (Jurnal Ilmiah Ekonomi Islam, 2023)
Accounting information is a computer-based system and determines performance appraisal, performance, and usage. Accounting information is very important to use in BAZNAS, because if you don't use an accounting information system, the reporting system or budget arrangement will not be optimal. Based on the acceptance data for the last 5 years from the results of interviews, it was found that the data on receipt of zakat funds at BAZNAS has experienced ups and downs or is unstable, so this will affect public confidence in giving zakat at BAZNAS. Zakat funds are trust funds that are paid by the community to be distributed to mustahik. This study aims to analyze the application of accounting information and assess the level of acceptance of zakat funds at the Medan City National Amil Zakat Agency. This research method uses a qualitative approach with descriptive methods and the research data consists of primary data and secondary data. In this study, the primary data was obtained from direct observations and interviews with informants, while the secondary data in this study were in the form of research supporting data, such as documents owned by BAZNAS in the city of Medan. The results showed that the implementation of the Medan City BAZNAS information system was in accordance with PSAK no 109 in the sense of Statement of Financial Accounting Standards (PSAK) no 109 regarding zakat and infaq/alms accounting issued by the Indonesian Institute of Accountants (IAI). PSAK no. 109 is used as a guideline for OPZ (zakat management organization) in the recognition, measurement, presentation and disclosure of zakat and infaq/alms transactions. The level of receipt of BAZNAS zakat funds in Medan City shows an unstable condition, where there are changes every year, it can go up or down. Judging from the report on changes in zakat funds in 2018 Rp. 709,759,592, in 2019 Rp. 310,816,859, in 2020 Rp. 653,352,697, in 2021 Rp. 738,399,810, and in 2022 Rp. 1,737,062,598.